DEVELOPMENT OF MICROSTRIP YAGI ANTENNA FOR 4G COMMUNICATION APPLICATION - YIP, JENN HUEI (IRC, 2019)
In wireless technology, microstrip Yagi antenna is one of the recent technologies that are used to obtain an efficient performance of the antenna. The main purpose of this project is to simulate and design a Microstrip Yagi antenna prototype for 4G communication applications. The main problem faced in this project is the microstrip Yagi antenna is having a narrow impedance bandwidth which is not suitable for board bandwidth applications. Therefore, in this project some research on the techniques for bandwidth enhancement and obtaining a good return loss are studied. The design of the microstrip Yagi antenna prototype is created and simulated using the Computer Simulation Technology (CST) software to achieve the desired frequency band, a good return loss and a wider bandwidth. The expectation of the microstrip Yagi antenna is to obtain a wider bandwidth and a higher gain with an operating frequency range within 4G Long-Term Evolution (LTE) frequency band. To demonstrate the idea, the wireless area network (WLAN) within 4G LTE frequency band is used to design the Microstrip Yagi antenna prototype. Several parametric studies of the proposed configuration were carried out to characterize the antennas and to verify the simulation result. The final result produces a good return loss and bandwidth which operates at frequency of 2.668 GHz with impedance bandwidth of 0.272 GHz. The antenna is fabricated and the performance of the antenna is tested and measured. The result shows a closed agreement with simulated result.